Cover crops in livestock systems: biomass production and effects on soil (Semiárida, 2024)
The inclusion of green fodder as cover crops (CC) in rotations with high silage frequency is strategic to generate cover, reduce erosion processes and improve the balance of organic matter in the soil. The objective was to evaluate the effects of the inclusion of CC of rye and vetch for 7 years, on the apparent density and water infiltration in the soil in a livestock system with high frequency of corn silage. The treatments were established as a fallow without CC (T), rye (Ce), fertilized rye (Ce+N), vetch (V) and consociation of vetch with rye (VCe). The CC were sown between corn crops that were destined for silage. The CC of Ce+N and VCe stood out for reaching the highest production of accumulated biomass during 7 years, being 41,034 and 39,361 kg dry matter (MS) ha-1, respectively. The production of accumulated aboveground biomass in the corn crop was higher in the treatments that included CC, compared to the treatment without CC. The inclusion of CC affected the soil bulk density, being lower compared to the T situation. The Ce treatment presented greater water infiltration in the soil (148 mm h-1) than V (118 mm h-1), and both were significantly different from T (73 mm h-1).
Keywords: rye; vetch; corn for silage; infiltration